2020
DOI: 10.1002/kjm2.12175
|View full text |Cite
|
Sign up to set email alerts
|

Cervical neoplastic lesions in relation to CD4 T‐lymphocyte counts and antiretroviral therapy among women with clinical stage 1 HIV in Yunnan, China

Abstract: China lacks data demonstrating associations of cervical neoplastic lesions with CD4 T‐lymphocyte (CD4 cell) counts and antiretroviral therapy (ART) among HIV‐infected women, suggesting relevant investigations are needed. A total of 545 HIV‐infected women were enrolled in Yunnan, China, between 2011 and 2013. CD4 cell counts and ART were measured via medical records and cervical neoplastic lesions were measured by professional pathologists. Multivariable logistic models, which treated cervical intraepithelial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…It is possible that early initiation with antiretroviral therapy can lower the incidence and progression of premalignant lesions 27. This study confirmed the findings of other studies that have shown different prevalence distributions in women with different CD4 count categories, despite the small number of patients with CD4 counts of <200 cells/mm 3 in this study 28 29…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that early initiation with antiretroviral therapy can lower the incidence and progression of premalignant lesions 27. This study confirmed the findings of other studies that have shown different prevalence distributions in women with different CD4 count categories, despite the small number of patients with CD4 counts of <200 cells/mm 3 in this study 28 29…”
Section: Discussionsupporting
confidence: 90%
“…Thirteen studies enrolled WLHIV attending cervical cancer screening in outpatient gynaecology clinics, 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 whereas 21 studies recruited WLHIV attending HIV clinics. 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Two studies recruited WLHIV with a prior positive screen-test (HPV-positive) 58 , 59 and two studies included a combination of women attending primary care and women referred to colposcopy because of positive HPV test and/or abnormal cytology. 60 , 61 The median age of enrolled women within studies ranged from 30 to 50 years (age range: 19 to 68 years).…”
Section: Resultsmentioning
confidence: 99%
“… 25 , 29 , 30 , 32 , 36 , 37 , 39 , 41 , 42 , 45 , 47 , 48 , 51 , 53 . Twenty-eight studies evaluated any HR-HPV DNA test method for CIN2+ 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 46 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 60 and 18 for CIN3+; 25 , 28 , 29 , 30 , 33 , 36 , 37 , 39 , 41 , 42 , 45 , 47 , 49 , 50 , 51 , 53 , 60 , 61 these included Hybrid Capture II (HC-II; 16 studies); 27 , 29 , 31 , 34 , 35 , 36 , 37 , 40 ...…”
Section: Resultsmentioning
confidence: 99%
“…The study by Zhang et al on the association of cervical neoplastic lesions with CD4 cell counts and the use of ART among HIV-infected women found that the prevalence of cervical neoplasia appeared to be higher in women who had lower CD4 cell counts. The authors concluded that high CD4 cell counts might have protective effects against the development of cervical neoplastic lesions [ 22 ]. Low CD4 cell counts in HIV-infected women indicate the existence of immunosuppression, which can be associated with an increased risk of cervical neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…However, such results might be limited by the small number of 20 HIV-positive women in each group. A population-based study among 545 HIV-infected women in China reported no significant interaction between CIN development and duration of HIV infection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%